Prisoners' Dilemma in Duopoly Supergames - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
The choice between quantity and price in order to stabilize collusion is modeled here. It is shown that this relocates the prisoners' dilemma backwards, from the market stage to the stage where the market variable is chosen in order to sustain collusion, and where discount rates appear as the payos. Likewise, a prisoners' dilemma arises also when both the market variable and the type of behavior (cooperative or non-cooperative) are simultaneously chosen.
Keywords: 330